K Coverage Probability of 5G Wireless Cognitive Radio Network under Shadow Fading Effects - Ankur S. Kang; Renu Vig (IAES Indonesian Section, 2016)
Land mobile communication is burdened with typical propagation constraints due to the channel characteristics in radio systems.Also,the propagation characteristics vary form place to place and also as the mobile unit moves,from time to time.Hence,the tramsmission path between transmitter and receiver varies from simple direct LOS to the one which is severely obstructed by buildings,foliage and terrain.Multipath propagation and shadow fading effects affect the signal strength of an arbitrary Transmitter-Receiver due to the rapid fluctuations in the phase and amplitude of signal which also determines the average power over an area of tens or hundreds of meters.Shadowing introduces additional fluctuations,so the received local mean power varies around the area –mean.The present section deals with the performance analysis of fifth generation wireless cognitive radio network on the basis of signal and interference level based k coverage probability under the shadow fading effects.